UNCTAD. World Investment Report 2000: Cross-border Mergers and Acquisitions and Development. New York: UNCTAD, 2000. xviii+337 pages. Paperback. Price not given. (The Pakistan Development Review, 2001)
Foreign aid has given way to foreign direct investment (FDI) as a means of stimulating growth in not only the developed countries but also the developing ones. FDI can be divided into two components: direct and portfolio. Direct investment is concerned with the establishment of physical assets in the shape of plants and equipment which in turn are used to produce commodities. The establishment of plants and equipment involves technology and raises the issue of technology transfer. Portfolio investment, on the other hand, is largely financial, with investments being made on the stock market. These investments, given the interlinkages between the main financial centres these days, are volatile because international capital is highly mobile. Both direct and portfolio investment can be made by public authorities, multinational firms, and individuals.